Incidence of Hydro Pericardium Syndrom Disease in Broilers of Hyderabad, Sindh - Memon, Zaibun-Nisa; Gachal, G.S.; Yusuf, M.; Arian, M. Akbar (International Journal of Poultry Science, 2006)
Hydro pericardium syndrome (HPS) is an important, recently emerged, disease of poultry, particularly of –6 week old age broilers chicks, characterized by its sudden onset, with high mortality ranging from 20-70%, typically hydro pericardium and mottled and friable livers, with intranuclear inclusion bodies in the hepatocytes. The liver of the infected birds shows necrotic foci and basophilic intra nuclear inclusion bodies in the hepatocytes and pinpoint white foci in the pancreases and ventricular erosions in broilers. The disease has been controlled by the use of formaline-inactivated vaccines, prepared from infected liver homogenate and of inactivated cell culture vaccines. The present study was conducted to determine the incidence of hydro pericardium syndrome disease at different broiler farms of Hyderabad district. Data were collected between 1999 to 2001 from 25 commercial broiler farms. The survey was made at regular intervals for the presence of Hydropericardium Syndrome disease and from the official record of the Disease Diagnostic Laboratory of Directorate of Poultry Production, Hyderabad.